The cell biology of fertilization: Gamete attachment and fusion - Siu, Karen K.; Serrão, Vitor Hugo B.; Ziyyat, Ahmed; Lee, Jeffrey E. (The Journal of cell biology, 2021)
Fertilization is defined as the union of two gametes. During fertilization, sperm and egg fuse to form a diploid zygote to initiate prenatal development. In mammals, fertilization involves multiple ordered steps, including the acrosome reaction, zona pellucida penetration, sperm–egg attachment, and membrane fusion. Given the success of in vitro fertilization, one would think that the mechanisms of fertilization are understood; however, the precise details for many of the steps in fertilization remain a mystery. Recent studies using genetic knockout mouse models and structural biology are providing valuable insight into the molecular basis of sperm–egg attachment and fusion. Here, we review the cell biology of fertilization, specifically summarizing data from recent structural and functional studies that provide insights into the interactions involved in human gamete attachment and fusion.